Sarcopenic obesity and the risk of hospitalization or death from coronavirus disease 2019: findings from UK Biobank. Issue 1 (3rd July 2021) - Wilkinson, Thomas J.; Yates, Thomas; Baker, Luke A.; Zaccardi, Francesco; Smith, Alice C.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2. The role of skeletal muscle mass in modulating immune response is well documented. Whilst obesity is well established as a key factor in COVID‐19 and outcome, no study has examined the influence of both sarcopenia (low muscle mass) and obesity, termed 'sarcopenic obesity' on the risk of severe COVID‐19. Methods: This study uses data from UK Biobank. Probable sarcopenia was defined as low handgrip strength. Sarcopenic obesity was mutually exclusively defined as the presence of obesity and low muscle mass [based on two established criteria: appendicular lean mass (ALM) adjusted for either (i) height or (ii) body mass index]. Severe COVID‐19 was defined by a positive severe acute respiratory syndrome coronavirus 2 test result in a hospital setting and/or death with a primary cause reported as COVID‐19. Fully adjusted logistic regression models were used to analyse the associations between sarcopenic status and severe COVID‐19. This work was conducted under UK Biobank Application Number 52553. Results: We analysed data from 490 301 UK Biobank participants (median age 70.0 years, 46% male); 2203 (0.4%) had severe COVID‐19. Individuals with probable sarcopenia were 64% more likely to have had severe COVID‐19 (odds ratio 1.638; P  < 0.001). Obesity increased the likelihood of severe COVID‐19 by 76% ( P  < 0.001). Using either ALM index or ALM/body mass index to define low muscle mass, those with sarcopenic obesity were 2.6 times more likely to have severe COVID‐19 (odds ratio 2.619; P  < 0.001). Sarcopenia alone did not increase the risk of COVID‐19. Conclusions: Sarcopenic obesity may increase the risk of severe COVID‐19, over that of obesity alone. The mechanisms for this are complex but could be a result of a reduction in respiratory functioning, immune response, and ability to respond to metabolic stress.